AN EXPLORATORY STUDY ON THE CHARACTERISTICS OF DRIVERS’ PREFERRED SEAT POSITIONS - Jung, Jaemoon; Park, Woojin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Among many vehicle interior components, the one that interacts with the driver continuously at all times is the driver’s seat. Many studies and standards have utilized driver-selected seat positions (DSSPs) as a basis for evaluating vehicle interior designs for driver comfort and safety. However, little research has examined the basic characteristics of DSSPs. This study analyses empirically obtained DSSPs to explore their geometric, mathematical and statistical properties. Six indices pertinent to the size, shape, orientation and location of each individual’s DSSP point cloud are employed. The normality of the DSSP point clouds and possible correlational relationships among the indices and those between the indices and selected anthropometric dimensions are statistically tested. The results suggest that 1) DSSP prediction and modeling must reflect the unimodal, non-normal nature of DSSP distributions and the correlational structures identified, and 2) both inter-individual/intra-individual variability in DSSPs need to be considered in designing and evaluating seat adjustability features.